2010
DOI: 10.3109/02770903.2010.491147
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Exhaled Nitric Oxide for Diagnosing Asthma

Abstract: Patients with confirmed asthma showed higher FeNO levels. A cut-off value of 40 ppb was calculated as the most efficient for asthma diagnosis in our population. The use of FeNO measurement may be a helpful tool to rule out a diagnosis of asthma, especially in patients in whom a methacholine challenge is not feasible or available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 15 publications
2
47
0
2
Order By: Relevance
“…Since the risk of bias was unclear or high in about half of the studies, the SOE was rated down to moderate. Using Deeks' funnel plot asymmetry tests and visual inspection of funnel plots, we found potential publication bias for cutoffs<20, and no indication of publication bias for cutoffs [20][21][22][23][24][25][26][27][28][29][30] (Appendix Figures D.10-11). We were not able to evaluate potential publication bias for other cutoffs.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Since the risk of bias was unclear or high in about half of the studies, the SOE was rated down to moderate. Using Deeks' funnel plot asymmetry tests and visual inspection of funnel plots, we found potential publication bias for cutoffs<20, and no indication of publication bias for cutoffs [20][21][22][23][24][25][26][27][28][29][30] (Appendix Figures D.10-11). We were not able to evaluate potential publication bias for other cutoffs.…”
Section: )mentioning
confidence: 99%
“…We did not rate down for statistical heterogeneity (which is always high in diagnostic meta-analyses) or consider diagnostic accuracy measures as surrogate outcomes. 28,29 When studies were heterogeneous in population, intervention and methods; and not appropriate for meta-analysis, we have narratively provided a summary statement about the findings and conveyed our certainty in such findings as a SOE rating. [30][31][32] In this case and in the absecnce of a single pooled estimate of the effect size, we narratively rated the SOE considering the meaning and connotation of SOE domains (methodological limitations of the studies, precision, directness, consistency and the likelihood of publication bias).…”
Section: Grading the Strength Of Evidence For Major Comparisons And Omentioning
confidence: 99%
“…Adults, adults plus adolescents, all age groups and unspecified age groups ), adults plus adolescents (three studies, four citations [82][83][84][85] ), all age groups (three studies, three citations [86][87][88] or an unspecified age range (three studies, three citations 89,90,92 ). Table 21 summarises the characteristics of the studies and provides a brief description explaining their relevance to the decision problem (note: Schneider et al 71,72 appears twice in this table as this study reported two differently defined populations).…”
Section: Diagnostic Reviewmentioning
confidence: 99%
“…It is not surprising that published results on FeNO50 during baseline and during methacholine challenge produced conflicting data. Most studies have reported only modest relationships between PD20 and FeNO50 [11,[24][25][26]. Further complication could arise if the exhaled maneuver is influenced by changes in gas distribution due to broncho constriction [27] or if expiratory flow rates exceed 150 ml/sec [28].…”
Section: Discussionmentioning
confidence: 99%
“…It has become clearer that NO levels in the exhaled gas involves a complicated series of events and depends on the severity of inflammation, location of inflammation and type of inflammatory cells involved [10]. It remains unclear if exhaled NO bears any relationship to pulmonary function, airway inflammation or airway reactivity in all asthmatics [11]. Taylor et al [12] suggested that in mild asthmatics, endogenous NO neither protects against nor contributes to the processes underlying airways responses to inhaled allergens.…”
Section: Introductionmentioning
confidence: 99%